Cognitive Maps: Encoding and Decoding Information - Lloyd, Robert (Annals of the Association of American Geographers, 1989)
The experiences of learning a city by direct experience or navigating through it and studying a map of it provide people with different types of spatial information. Navigation is thought to provide procedural knowledge, which is stored as verbal coding, and map reading is thought to provide survey knowledge, which is stored as imagery coding. Subjects who learned a city primarily through years of navigation and subjects who learned a city by studying a cartographic map for several minutes were asked to perform the simple experimental task of locating familiar landmarks relative to reference points. Distortions in the cognitive maps of subjects were analyzed to determine significant differences in patterns of distance and direction errors. Patterns of absolute distortion are explained by theories related to the use of alignment and rotation heuristics for encoding information and an implicit scaling process for decoding information. Subjects who learned the city from studying a cartographic map were significantly more accurate and faster at performing the experimental task than subjects who learned the city through direct experience or navigation. Both groups were significantly more accurate when making their judgments with centrally located reference points than with peripherally located reference points. These results provide knowledge of processes used in cognitive mapping and the distortions caused by these processes. Ultimately such studies lead to an understanding of spatial decision-making and behavior.